ALAT PAKAN IKAN KONTROL JARAK JAUH PADA AQUARIUM MENGGUNAKAN INFORMASI APLIKASI TELEGRAM BERBASIS ARDUINO: Pentingnya memberi pakan ikan tepat waktu - Ahmad fariz safriansyah (Jurnal Qua Teknika, 2024)
The use of technology in the fisheries sector has shown great potential to improve efficiency and productivity. This research aims to develop and implement an automatic fish feed device integrated with an Arduino-based Telegram application. The system is designed to provide feed automatically according to a specified schedule and allows remote control via Telegram application. The research method involves designing hardware using Arduino, developing software for control via Telegram, and testing the performance of the tool in a fish farming environment. The results show that this automatic fish feed device is able to provide feed in a timely manner and quantity according to the needs of the fish, and can be efficiently controlled remotely using the Telegram application. Functionality and reliability tests were conducted by simulation in the laboratory as well as field tests in fish farming ponds. The data collected shows that this system not only improves feeding efficiency, but also reduces the manual workload of fish farmers. The conclusion of this study is that an Arduino-based automatic fish feed device integrated with Telegram application can be an effective solution for feeding management in fish farming. It provides significant benefits in terms of time savings, improved operational efficiency, and remote control capabilities. This research is expected to be the basis for further development in the application of automation technology in the fisheries sector.Keywords: Telegram App, Arduino, Remote Control, Operational Efficiency